Trash or Treasure: extracellular microRNAs and cell-to-cell communication - Kosaka, Nobuyoshi; Yusuke, Yoshioka; Hagiwara, Keitaro; Tominaga, Naoomi; Katsuda, Takeshi; Ochiya, Takahiro (Frontiers in Genetics, 2013)
Circulating RNAs in human body fluids are promising candidates for diagnostic purposes. However, the biological significance of circulating RNAs remains elusive. Recently, small non-coding RNAs, microRNAs (miRNAs), were isolated from multiple human body fluids, and these “circulating miRNAs” have been implicated as novel disease biomarkers. Concurrently, miRNAs were also identified in the extracellular space associated with extracellular vesicles (EVs), which are small membrane vesicles secreted from various types of cells. The function of these secreted miRNAs has been revealed in several papers. Circulating miRNAs have been experimentally found to be associated with EVs, however, other types of extracellular miRNAs were also described. This review discusses studies related to extracellular miRNAs, including circulating miRNAs and secreted miRNAs, to highlight the importance of studying not only secreted miRNAs but also circulating miRNAs to determine the contribution of extracellular miRNAs especially in cancer development.